Tea in health and disease prevention - Preedy, Victor R. (Elsevier, 2013)
While there have been many claims of the benefits of teas through the years, and while there is nearly universal agreement that drinking tea can benefit health, there is still a concern over whether the lab-generated results are representative of real-life benefit, what the risk of toxicity might be, and what the effective-level thresholds are for various purposes. Clearly there are still questions about the efficacy and use of tea for health benefit. This book presents a comprehensive look at the compounds in black, green, and white teas, their reported benefits (or toxicity risks) and also explores them on a health-condition specific level, providing researchers and academics with a single-volume resource to help in identifying potential treatment uses. No other book on the market considers all the varieties of teas in one volume, or takes the disease-focused approach that will assist in directing further research and studies. Interdisciplinary presentation of material assists in identifying potential cross-over benefits and similarities between tea sources and diseases Assists in identifying therapeutic benefits for new product development Includes coverage and comparison of the most important types of tea - green, black and white
Description based on title from publisher data
Keywords: Electronic books; Präventivmedizin; Tee; Naturheilmittel